PENGARUH VARIASI WAKTU DAN KECEPATAN UDARA PANAS TERHADAP PERFORMA PENGERINGAN IKAN BAGE TIPE TRAY DRYER BAHAN BAKAR GAS LPG: THE EFFECT OF TIME VARIATION AND SPEED OF HOT AIR ON THE DRYING PERFORMANCE OF TRAY DRYER TYPE BAGE FISH LPG GAS FUEL - Heri; Anggara, Mitra (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
The processed production of lemuru fish is used as a typical food of Sumbawa which goes through a drying process. When something is dried, heat is transferred in an inefficient manner due to the uneven distribution of fluid flow from the heating furnace and blower to the drying rack. The purpose of this study is to examine so that the transfer of hot air that is channeled can be evenly distributed on each shelf to dry during drying. This study used independent variables, bound variables and controlled variables using a randomized design (RAL) with 3 experiments. The results showed that the highest drying rate was produced at 180 minutes with an air speed of 2 m / s of 0.64 g / minute. Testing of bage fish moisture content in accordance with the quality standards of dried salted fish (SNI 8273: 2016) occurred in drying treatment with a time of 300 minutes with hot air speeds of 1.5 m / s (38.67%), and 2 m / s (37.89%). The highest drying efficiency was found at 180 minutes with a hot air speed of 2 m/s of 0.703%.